Remodeling the hepatic fibrotic microenvironment with emerging nanotherapeutics: a comprehensive review - Xingtao Zhao; Felix Kwame Amevor; Xinyan Xue; Cheng Wang; Zhifu Cui; Shu Dai; Cheng Peng; Yunxia Li (Journal of Nanobiotechnology, 2023)
Abstract Liver fibrosis could be the last hope for treating liver cancer and remodeling of the hepatic microenvironment has emerged as a strategy to promote the ablation of liver fibrosis. In recent years, especially with the rapid development of nanomedicine, hepatic microenvironment therapy has been widely researched in studies concerning liver cancer and fibrosis. In this comprehensive review, we summarized recent advances in nano therapy-based remodeling of the hepatic microenvironment. Firstly, we discussed novel strategies for regulatory immune suppression caused by capillarization of liver sinusoidal endothelial cells (LSECs) and macrophage polarization. Furthermore, metabolic reprogramming and extracellular matrix (ECM) deposition are caused by the activation of hepatic stellate cells (HSCs). In addition, recent advances in ROS, hypoxia, and impaired vascular remodeling in the hepatic fibrotic microenvironment due to ECM deposition have also been summarized. Finally, emerging nanotherapeutic approaches based on correlated signals were discussed in this review. We have proposed novel strategies such as engineered nanotherapeutics targeting antigen-presenting cells (APCs) or direct targeting T cells in liver fibrotic immunotherapy to be used in preventing liver fibrosis. In summary, this comprehensive review illustrated the opportunities in drug targeting and nanomedicine, and the current challenges to be addressed. Graphical Abstract